Formulation and Evaluation of Growth Hormone-Carrying Hydrogel Containing Chitosan and Polyvinyl Alcohol for Wound Healing - Nazerian, Shiva; Darabian, Bita; Bagheri, Hamed; Sahebghadam Lotfi, Abbas (Iranian Journal of Pharmaceutical Sciences, 2024)
Wound healing is an important issue related to health. Due to lifestyle changes, population growth, and disease patterns, it is necessary to propose methods for efficient wound healing. In this study, a novel hydrogel dressing is offered containing Chitosan (CN) and Polyvinyl alcohol (PVA) polymers chemically cross-linked by Genipin (GN) and using Glycerol (G) as a softener. Somatropin is used to directly affect collagen formation and the acceleration of the healing process. The morphology was evaluated using SEM, and the effect of each component on properties (e.g., softness, roughness, and crystallinity) was examined. Evaluating mechanical properties showed the effect of PVA and G on the hydrogel’s elongation, strength, and elastic modulus. The most similar sample to skin was also introduced. Differential scanning calorimetry (DSC) was performed, and the effect of components on crystal structure and thermal properties was investigated. FTIR was conducted to identify organic compounds and their functional groups to ensure the compatibility of CN, PVA, and somatropin. In vitro, degradation tests showed the biodegradability of samples, and the most appropriate degradation rate was determined. Findings show the direct effect of PVA and G on water absorption rate. Investigating the pH changes during degradation revealed that this rate positively affects the wound-healing process. In the drug-release test, G-containing samples exhibited better performance and had a higher release rate in the first four days of healing, when the wound needed the highest growth hormone. MTT assay evaluated the cytotoxicity of samples. According to the results, cell growth and survival percentages were higher in the drug-containing samples.